Design and Implementation of the Korean Muallaf Center Applications as a Guide to Procedures for Praying for Korean - W A A Praditasari; I Kholis; A A Budiman (INSIST, 2018)
Based on data analysis proved that during 20152060, the number of Muslim population increased rapidly by increasing 70%, which is included converts in South Korea. The developments of Islam in South Korea characterized by the growing mosque of Seoul, Itaewon Mosque Islamic Center. The main constraint factor for Korean converts is there is still no prayer guide in Hangeul feature. Constraints experienced by converts, most important is prayer. The Korean Muallaf Center is an application that helps converts to include wudu, prayers, and easy-to-understand religious worship. The purpose of this research is to help converts to understand the guidelines of Islam with Hangeul, so that they can practice it. The methodology of this research is with literature study, application design, implementation, and evaluation of application usage. The results of this study are the Korean Muallaf Center Applications that have been used by Muallaf Korea.